Klašu un instanču diagrammu redaktora izstrāde, izmantojot rīku definēšanas platformu GrTP - Rikters, Matīss (Latvijas Universitāte, 2010)
Šis kvalifikācijas darbs izstrādāts saistībā ar programmēšanas praksi Latvijas Universitātes Matemātikas un informātikas institūtā. Darba mērķis bija izstrādāt programmatūru, ar kuru ir ērti zīmēt un strādāt ar klašu un instanču diagrammām. Programmatūra ļauj lietotājam zīmēt diagrammas elementus, palīdz lietotājam, piedāvājot izvēlēties vērtības elementu laukos, kā arī pārbauda, vai dati, ko lietotājs ievadījis elementu laukos, ievadīti korektā formātā, un, vai pati diagramma sastādīta korekti.

This qualification work was developed in association with programming practice in the Institute of Mathematics and Computer Sciences, University of Latvia. The objective of this work was to develop an easy to use program for drawing and working with class and instance diagrams. The program allows the user to draw the diagram elements, offers input values for the diagram elements, and also checks whether the values that the user has input are in the correct format and whether the diagram itself is composed correctly. Keywords: classes, instances, diagrams, metamodels, modeling Abstract This qualification work was developed in association with programming practice in the Institute of Mathematics and Computer Sciences, University of Latvia. The objective of this work was to develop an easy to use program for drawing and working with class and instance diagrams. The program allows the user to draw the diagram elements, offers input values for the diagram elements, and also checks whether the values that the user has input are in the correct format and whether the diagram itself is composed correctly.
The development of a class and instance diagram editor using the tool defining platform GrTP
Keywords: Datorzinātne